Influence of Er,Cr:YSGG Laser Surface Treatments on Micro Push-Out Bond Strength of Fiber Posts to Composite Resin Core Materials - Ghavami-Lahiji M; Benedicenti S; Karimian R; Shahabi S (Shiraz University of Medical Sciences, 2018)
Statement of problem: The bonding of fiber post to resin core or root dentin is challenged by limited penetration of resin material to the polymeric matrix of fiber posts. Objectives: The purpose of this study was to investigate the effect of Er,Cr:YSGG on micro push-out bond strength of glass fiber posts to resin core material. Materials and Methods: We used 2 commercially available fiber posts, Exacto (Angelus) and White Post DC (FGM), which had similar coronal diameters. Specimens of each fiber post (n=36) were randomly divided into three subgroups (n=12 posts per group) according to different surface treatment methods: control (no surface treatment), irradiation by 1W Er,Cr:YSGG, and irradiation by 1.5W Er,Cr:YSGG. A cylindrical plastic tube was placed around the post. Resin core material was filled into the tube and cured. Coronal portions of the posts were sectioned into 1-mm-thick slices. Then, the specimens were subjected to a thermocyling device for 3000 cycles. The micro push-out test was carried out using a Universal Testing Machine. Data were analyzed using one-way ANOVA followed by Tukey's HSD post hoc test to investigate the effect of different surface treatments on each type of fiber post. Results: The 1.5W Er,Cr:YSGG laser statistically reduced micro push-out bond strength values in the Exacto groups (P<0.05). However, there was no significant difference between the control and 1W Er,Cr:YSGG groups. We observed no significant difference among different surface treatment methods in the White post DC groups (P>0.05). Mode of failure analysis showed that mixed failure was the predominant failure type for all surface treatment groups. Conclusions: The beneficial effect of Er,Cr:YSGG laser application could not be confirmed based on the results of this in vitro study. Er,Cr:YSGG laser could not significantly enhance the bond strength values. However, the 1.5W laser statistically decreased micro push-out bond strength in the Exacto fiber posts.